(3EUMGMGJ GdbOjS eJis - (3GdbOjS eJjs
(3ChdgG (B:s
(3fHJOF HYhf Gddg hMSf Jhajbg hEQTGOg fcJH GdCQHYI CfGLjd GdebOSI GdChd ef Pdc HTGQI GdbOjS eJi GdCfLjdi Chd bQGAg efg djhe GdCMO bHd GdejdGO GdeLjO cJGH ehdO EjShY ddeSjM Hf OGhO Hf EHQGgje s
(3BNQgG (B:s
(3CWdH GdYde jGaJG EfeG GdYde HGdWdH hGOYi def bQC fYe hdef cJH jG QH EQMefG jG NjQ eWdhH hCcQe WdH EZaQ dUGMHg fYe hddcGJH s
(3cJHJ HYV GdcdeGJ HGdMeQIs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdOjGfGJ GdCNQis